Microcantilever chaotic motion suppression in tapping mode atomic force microscope - Balthazar, José Manoel [UNESP]; Tusset, Angelo Marcelo; De Souza, Silvio Luiz Thomaz; Bueno, Atila Madureira (SAGE Publications, 2013)
The tapping mode is one of the mostly employed techniques in atomic force microscopy due to its accurate imaging quality for a wide variety of surfaces. However, chaotic microcantilever motion impairs the obtention of accurate images from the sample surfaces. In order to investigate the problem the tapping mode atomic force microscope is modeled and chaotic motion is identified for a wide range of the parameter's values. Additionally, attempting to prevent the chaotic motion, two control techniques are implemented: the optimal linear feedback control and the time-delayed feedback control. The simulation results show the feasibility of the techniques for chaos control in the atomic force microscopy. © 2012 IMechE.
Keywords: Atomic force microscopy; chaos; control; nonlinear dynamics; tapping mode atomic force microscope; Chaotic motions; Control techniques; Imaging quality; Linear feedback control; Micro-cantilevers; Sample surface; Tapping modes; Time-delayed feedback; Chaos theory; Chaotic systems; Composite micromechanics; Control; Dynamics; Feedback control